STUDI PENERAPAN KONSEP EKO HIDRAULIK UNTUK MITIGASI BANJIR DI SUNGAI PULISAN - Muhammad Mufli Fajar; Tiny Mananoma; Jeffry S. F. Sumarauw (STKIP PGRI Situbondo, 2024)
The analysis began by finding the frequency of rain using the Log Pearson III method. The rain data used came from two rain posts, namely the Araren-Pinenek MRG rain post and the Maen Climatology rain post. The rainfall data used is the maximum daily rainfall data from 2002 to 2019. Rain flow modeling on the HEC-HMS komputer program using the HSS Soil Conservation Services method, and for water loss with the SCS Curve Number (CN). For baseflow using the recession method. HSS SCS parameter calibration was performed before simulating flood discharge using peak discharge test. The calibrated parameters are lag time, curve number, recession constant, initial discharge and ratio to peak. For the limits of each parameter is adjusted to the standard values in the HEC-HMS komputer program. The peak discharge test results show 2.2 m3 / second. Then a flood discharge analysis was carried out with calibrated parameters using the HEC-HMS komputer program. The peak discharge results simulated each time are re-entered in the HEC-RAS komputer program, then simulating flow profiles including flow velocity and high elevation of the water table. The flood discharge plan used is the 25 years period of 24,5 m3/second by installing several Eco Hydraulic constructions such as vetiver grass, bush grass, bamboo plants, logs, and a combination of vetiver grass and logs. The flow speed of the existing cross-section with the application between vetiver grass and logs can be reduced by 62%. With the use of Eco Hydraulics, it can reduce and optimize flow speed and looks aesthetic considering Pulisan is a superpriority area